Effect of losses on optical properties of chiral metamembranes - Valenko, N.V.; Dmitrieva, O.A.; Tikhodeev, S.G. (Kompʹûternaâ optika, 2024)
An optical response (reflection, transmission, and absorption spectra) of a photonic crystal layer with a square lattice of chiral holes with rotation axis C2 to circularly polarized light is theoretically investigated. The geometrical parameters of the structure are selected to achieve the maximum possible circular dichroism response under the condition of complete absence of optical losses in the system. It is shown that the account of losses in thin near-surface layers of the structure, for example, due to scattering on surface roughness or absorption due to metallization of near-surface layers, leads to rapid degradation of the degree of chirality of the optical response, increasing the absorption value. Calculations are carried out for a chiral photonic crystal layer made of diamond for a wavelength range of λ=10–12 um (wave number, 830 – 1000 cm–1).